Exploring customer satisfaction in online food delivery services: The role of product involvement, brand familiarity, and consumer attitudes - Utari Dewi; Dimas Angga Negoro (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
The rise of online food delivery (OFD) services has significantly impacted consumer behavior, necessitating a deeper understanding of product involvement, brand familiarity, and consumer attitudes. Previous studies have explored these factors individually; however, this research aims to examine their collective impact on consumer satisfaction within the OFD sector. This study seeks to fill the gap by investigating how these variables influence consumer satisfaction, offering valuable insights for marketing strategies in the OFD industry. The main objective is to understand how product involvement, brand familiarity, and consumer attitudes contribute to consumer satisfaction. The study involved 154 users from various OFD platforms, including Go Food, Grab Food, and Shopee Food, selected through purposive sampling. The analysis was conducted using the structural equation model (SEM) to assess the relationships among the variables. Results indicate that product involvement does not influence consumer satisfaction; however, it has a positive influence on consumer attitude. Brand familiarity has a positive impact on attitude and consumer satisfaction. Consumer attitude has a po-sitive influence on consumer satisfaction. These findings suggest that enhancing brand familiarity and fostering positive consumer attitudes can significantly improve consumer satisfaction, therefore, offering a competitive advantage to OFD businesses.